PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Demijоv V.P. Transplante experimental de órganos vitales. Madrid: Editorial Atlante, 1967 - S. P. Glyantsev; Yu. G. Shatunova; A. Werner (Трансплантология (Москва), 2021)
For the first time, the article introduces into scientific circulation and analyzes the Preface by V.P. Demikhov to his book "Transplantation of vital organs in experiment", published in 1967 in Spanish under the title "Transplante experimental de órganos vitales". Judging by the facts mentioned in the text, V.P. Demikhov wrote it in 1966, reflecting his views on the current state and prospects of homoplastic tissue and organ transplantation. As in previous publications, in particular, in the Preface to the German edition of the book published in Berlin in 1963, V.P. Demikhov substantiated the concept that the main condition for a successful transplantation of homoplastic organs was to restore the blood circulation in them. In his opinion, the success of engraftment depends, first of all, on the ideally performed vascular suture and the immediate inclusion of the transplanted donor organ into the blood circulation of the host body, as well as on the sterility of the undertaken intervention. Having discussed the use of pharmacological immunosuppression as a method of overcoming the biological incompatibility of homologous organs during their transplantation, V.P. Demikhov pointed out the toxicity of the drugs used for this purpose he tested experimentally, as well as his experiments, indicating the possibility of overcoming incompatibility by means of other methods (the selection of the donor and recipient with regard to the blood group, mixing the blood of the donor and recipient by parabiosis, etc.). In this text V.P. Demikhov again mentioned the scheme he had developed for two-stage transplantation of an additional heart as a reserve organ to maintain the function of the patient's decompensated heart and named the main stages of the operation: implantation on the femoral vessels (stage 1) and transplantation into the chest (stage 2). As in the Preface to the German edition of the book, V.P. Demikhov spoke in detail about the model of a “living physiological system” he had developed in 1963 aimed at creating a bank of reanimated organs that would retain their viability until transplanted into another body. Projects for growing the organs in anencephalic newborns for the rejuvenation of the elderly were also outlined.